Involvement of Antioxidant System in the Amelioration of Scopolamine-Induced Memory Impairment by Grains of Paradise (Aframomum melegueta K. Schum.) Extract - Ishola, I. O.; Awoyemi, A. A.; Afolayan, G. O. (Drug Research, 2016)
Background: Grains of paradise (Aframomum melegueta) K. Schum is used to flavour foods and used as memory enhancer and anti-aging in traditional African medicine. This study examine the influence of ethanolic seed extract of Aframomum melegueta (AFM) on cognitive impairment induced by scopolamine in rodents.Methods: AFM (6.25, 12.5 or 25 mg/kg, p.o.) or tacrine (5 mg/kg, i.p.) was administered for 3 consecutive days, 1 h post-treatment on day 3, scopolamine (3 mg/kg, i.p.) was given, 5 min later, cognition was evaluated in the Y-maze and elevated plus maze (EPM) tests in mice as well as the Morris water maze (MWM) paradigm in rats. Biomarkers of oxidative stress in the prefrontal cortex, striatum and hippocampus of rats were evaluated after the MWM task. The antioxidant capacity of AFM was evaluated in vitro using the 1,1-diphenyl-2-picrylhydrazyl (DPPH), nitric oxide (NO) and ferric ion reducing power (FRAP) assays.Results: Scopolamine significantly reduced (38.72%) spontaneous alternation behavior in the Y-maze and increase in transfer latency in the EPM test on day 2, which was ameliorated by AFM (25 mg/kg; 49.86%, 71.55%, respectively) in mice. In addition, AFM prevented the spatial learning deficit induced by scopolamine in the MWM task. Similarly, scopolamine-induced oxidative-nitrosative stress was attenuated by AFM treatment, evidenced in decreased malondialdehyde and nitrite levels, restoration of glutathione and superoxide dismutase levels. Interestingly, AFM exhibited notable scavenging activities against DPPH, NO and FRAP radicals.Conclusion: These results showed that A. melegueta seed extract prevented scopolamine-induced memory impairments through enhancement of antioxidant defense systems.
Keywords: Aframomum melegueta; antioxidant systems; cognition deficit; memory; Morris water maze; Y-maze